Production of infectious hepatitis delta virus in vitro and neutralization with antibodies directed against hepatitis B virus pre-S antigens. - Sureau, C (1992)
Hepatitis delta virus (HDV) particles were produced in Huh7 human hepatoma cells by transfection with cloned hepatitis B virus (HBV) DNA and HDV cDNA. The particles were characterized by their buoyant density, the presence of encapsidated viral RNA, and their ability to infect primary cultures of chimpanzee hepatocytes. Successful infection was evidenced by the appearance of increasing amounts of intracellular HDV RNA after exposure to particles. Infection was prevented when particles were incubated with antibodies directed against synthetic peptides specific for epitopes of the pre-S1 or pre-S2 domains of the HBV envelope proteins before exposure to hepatocytes. These data demonstrate that HDV particles produced in vitro are infectious and indicate (i) that infectious particles are coated with HBV envelope proteins that contain the pre-S1 and pre-S2 regions, (ii) that epitopes of the pre-S1 and pre-S2 domains of HBV envelope proteins are exposed at the surface of HDV particles, and (iii) that antibodies directed against those epitopes have neutralizing activity against HDV.